Extended Inferior Turbinate Flap for Endoscopic Reconstruction of Skull Base Defects - Choby, Garret W.; Pinheiro-Neto, Carlos D.; de Almeida, John R.; Ruiz-Valdepeñas, Eugenio Cardenas; Wang, Eric W.; Fernandez-Miranda, Juan C.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective When the use of the nasoseptal flap for endoscopic skull base reconstruction has been precluded, the posterior pedicle inferior turbinate flap is a viable option for small midclival defects. Limitations of the inferior turbinate flap include its small surface area and limited arc of rotation. We describe a novel extended inferior turbinate flap that expands the reconstructive applications of this flap.Design Cadaveric anatomical study.Participants Cadaveric specimens.Main Outcome Measures Flap size, arc of rotation, and reconstructive applications were assessed.Results The average width of the flap was 5.46 ± 0.58 cm (7.32 ± 0.59 cm with septal mucosa). The average length of the flap was 5.01 ± 0.58 cm (5.28 ± 0.37 cm with septal mucosa). The average surface area of the flap was ∼ 27.26 ± 3.65 cm2 (40.53 ± 6.45 cm2 with septal mucosa). The extended inferior turbinate flap was sufficient to cover clival defects extending between the paraclival internal carotid arteries. The use of the flap in 22 cadavers and 5 clinical patients is described.Conclusion The extended inferior turbinate flap presents an additional option for reconstruction of skull base defects when the nasoseptal flap is unavailable.
Keywords: skull base reconstruction; endoscopic endonasal approach; inferior turbinate flap